Adsorption / catalysis bifunctional material for water-gas shift hydrogen production and preparation method of adsorption / catalysis bifunctional material

By crushing and acid leaching the steel slag, adsorption/catalytic dual-functional materials were prepared, which solved the problems of unutilized steel slag resources and high carbon emissions, and achieved efficient hydrogen production technology for water and gas conversion, promoting high yield and low carbon emissions of hydrogen.

CN119838614APending Publication Date: 2025-04-18TIANFU YONGXING LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510043133.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The lack of methods for using steel slag for water-gas conversion to produce hydrogen is caused by the failure of high-value recycling of steel slag resources, and the carbon emission problems caused by hydrogen production of fossil fuels have not been effectively solved.

Method used

By pulverizing and acid leaching the steel slag, the steel slag leaching solution rich in metal elements is extracted, and the adsorption/catalytic bifunctional material is prepared. The material exhibits efficient CO2 adsorption and CO conversion capabilities under 600°C, which promotes the progress of the hydrogen production reaction of water and gas transformation.

Benefits of technology

The high-value resource utilization of steel slag is realized, and a low-cost and efficient hydrogen production technology is provided, which can significantly improve the yield and purity of hydrogen and reduce carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838614A_ABST
    Figure CN119838614A_ABST
Patent Text Reader

Abstract

The invention provides an adsorption / catalysis bifunctional material for water-gas shift hydrogen production and a preparation method thereof.The preparation method comprises the steps that recycled steel slag is smashed and then subjected to acid leaching treatment to obtain a steel slag leaching solution, then any one or more of soluble ferric salt, manganese salt, calcium salt, magnesium salt and aluminum salt are added according to the leaching concentration of Fe, Mn, Ca, Mg and Al in the steel slag leaching solution, and the adsorption / catalysis bifunctional material for water-gas shift hydrogen production is obtained. Dropwise adding the obtained mixed solution into a sodium carbonate solution, controlling the pH value of the reaction solution, aging, separating, washing and drying to obtain a precursor solid, and roasting to obtain the adsorption / catalysis bifunctional material for water-gas shift hydrogen production. The adsorption capacity of the prepared adsorption / catalysis bifunctional material on CO2 at the temperature of 600 DEG C can reach 0.105 g / g, the CO conversion rate / hydrogen production rate can reach 83.1%, and the duration of a pre-breakthrough period is 2 h; a new way is provided for high-value recycling and reusing of the steel slag, and the method can be used as a foundation for follow-up technology development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts for water-gas shift hydrogen production, and relates to an adsorption / catalysis dual-function material for water-gas shift hydrogen production and a preparation method thereof, and specifically relates to a method for preparing the adsorption / catalysis dual-function material for water-gas shift hydrogen production based on steel slag leachate. Background Art

[0002] Hydrogen has a high calorific value and only produces water when oxidized, so it is considered an environmentally friendly energy carrier. The three major hydrogen production methods classified by raw materials are fossil fuel hydrogen production (such as natural gas reforming, glycerol reforming and coal gasification, etc.), industrial by-product hydrogen production and water electrolysis hydrogen production. At present, China has abundant coal resources and is limited by hydrogen production technology, so hydrogen is mainly obtained through the gasification or reforming of fossil fuels. According to data released by the China Hydrogen Energy Alliance, more than 98% of H2 in my country comes from fossil fuel hydrogen production, which is further produced using synthesis gas supplemented by the indispensable water-gas shift reaction. Although the energy conversion efficiency of this process can reach 80%, for every kg of H2 produced during its hydrogen production life cycle, CO2 emissions reach nearly 14 kg, which is not conducive to achieving the "dual carbon goals".

[0003] In recent years, biomass has attracted great attention due to its renewability and strong carbon reduction potential. The utilization methods of biomass include direct combustion technology, compact molding technology, biogas power generation technology and pyrolysis technology. Among the many biomass energy sources, forestry biomass is an indispensable part. Bamboo has become one of the precious forestry resources due to its strong renewable capacity, abundant output and good material quality. The utilization of bamboo resources in my country is mostly concentrated in industries with low added value such as food and building materials, resulting in low bamboo utilization rate and resource waste during processing. Therefore, it is of great significance to study and use new technical methods to deeply process bamboo raw materials and improve product quality to broaden the application field of bamboo. Bamboo pyrolysis technology can make clean use of bamboo. In an oxygen-free or low-oxygen environment, the biomass components are decomposed into coke, tar and small molecular gases by heat. Bamboo charcoal is an important product of bamboo pyrolysis, with a more abundant output. It can be used as a raw material for the preparation of high-performance activated carbon. The gas produced in the bamboo charcoal activation process contains a large amount of H2 and CO, which can be further converted into H2 through water-gas shift hydrogen production technology to realize its resource utilization.

[0004] The temperature of the synthesis gas produced during the activation of bamboo charcoal is relatively high, so the water-gas shift reaction needs to be carried out at a relatively high temperature. Since it is an exothermic reaction, high temperature is not conducive to the forward reaction. This limitation can be weakened by enhancing the water-gas shift reaction through in-situ adsorption of CO2. Based on the Le Chatelier principle, in-situ adsorption of CO2 can promote the forward movement of the equilibrium and increase the yield of hydrogen.

[0005] The selection of suitable adsorbents in the water-gas shift hydrogen production process is a key factor in producing high-purity hydrogen. Calcium, as an alkaline metal, has a high adsorption capacity for CO2 in its oxidized state, CaO. Theoretically, when fully converted, the adsorption capacity for CO2 can reach 17.86mmol / g. CaO also has a strong and fast CO2 capture capacity (600-700℃) and a large number of low-cost precursors, so it can be used as an excellent adsorbent in high-temperature water-gas shift reactions.

[0006] At the same time, the use of suitable catalysts can also promote the conversion of CO. Ni / CaO-based composite catalysts are widely used in adsorption-enhanced water-gas shift hydrogen production reactions because Ni exhibits excellent activity at high temperatures and CaO can quickly adsorb CO2. However, Ni is toxic and promotes methanation reactions, catalyzing the conversion of CO into byproduct CH4, thereby reducing the concentration of H2. Currently, Fe-based catalysts have been industrialized due to their low cost and durability. Fe-Cr catalysts are often used in high-temperature water-gas shift reactions, but the Cr component is still toxic and carcinogenic. Therefore, the development of chromium-free Fe-based catalysts with high activity and high stability is still a research hotspot in the field of water-gas shift hydrogen production.

[0007] Steel slag is the main solid waste generated in the steelmaking process, accounting for 15% to 20% of crude steel production. In 2021, my country's steel slag production reached 120 million tons, while the utilization rate of steel slag was only 20%, far lower than that of developed countries. A large amount of steel slag is abandoned, resulting in the waste of valuable materials or energy in it, and occupying land resources. The heavy metal elements in it will also cause damage to the environment. Compared with most other calcium sources, steel slag has obvious advantages due to its high Ca content and low cost. However, after investigation, there is no existing technology in the literature for applying steel slag to water-gas shift hydrogen production.

[0008] Therefore, if steel slag can be used in water-gas shift hydrogen production, it will not only achieve high-value resource utilization of steel slag, but also provide an efficient and low-cost industrial method for water-gas shift hydrogen production reaction in combination with bamboo pyrolysis technology. Summary of the invention

[0009] In order to solve the problems in the above-mentioned prior art, the present invention provides an adsorption / catalytic dual-functional material for water-gas shift hydrogen production and a preparation method thereof, which utilizes the proportion of each metal element in the steel slag leachate to prepare an adsorption / catalytic dual-functional material, and the adsorption amount of CO2 under 600°C temperature conditions can reach 0.105g / g, the CO conversion rate / hydrogen production rate can reach 83.1%, and the pre-breakthrough period duration is 2h; the present invention has excellent application prospects, provides a new way for high-value recovery and reuse of steel slag, and can serve as the foundation for subsequent technological development.

[0010] To achieve the above object, the present invention adopts a technical solution consisting of the following technical measures to achieve the above object. A method for preparing an adsorption / catalysis dual-function material for hydrogen production by water gas shift mainly comprises the following steps:

[0011] (1) subjecting the recovered steel slag to a pretreatment including crushing to obtain a powder to be leached with a particle size of 40 to 100 meshes;

[0012] (2) subjecting the powder to be leached obtained in step (1) to acid leaching to obtain a steel slag leachate;

[0013] (3) according to the leaching concentration of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate obtained in step (2), any one or more of soluble iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts are added to the steel slag leachate, so that the molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg in the obtained mixed solution meet 2.4-8, 20-21.55, 5-5.8 and 4-4.5 respectively, and the leaching concentration of calcium element is 10-18.2 g / L;

[0014] (4) adding the mixed solution obtained in step (3) and a 0.4-0.6 mol / L NaOH solution to a 0.1-0.2 mol / L NaCO3 solution simultaneously until the mixed solution is completely dripped, and during the dripping process, the pH of the reaction solution is controlled to be maintained at 10-11, to obtain a precursor solution;

[0015] The volume ratio of the mixed solution obtained in step (3) to the NaCO3 solution is 1:(0.7-1.3);

[0016] (5) aging the precursor liquid obtained in step (4) at 65 to 80° C. for 4 to 6 hours with stirring, and filtering, washing, and drying to obtain a precursor solid after the time is up;

[0017] (6) calcining the precursor solid obtained in step (5) to obtain an adsorption / catalytic dual-functional material for water gas shift hydrogen production;

[0018] The calcination is specifically carried out by heating the temperature to 500-550° C. at a rate of 2-5° C. / min and calcining for 3-4 hours.

[0019] In this article, the steel slag described in step (1) is an industrial solid waste generated during the steelmaking process. It should be noted that, depending on the different steelmaking processes, the steel slag produced has different particle sizes. Before recycling and reuse, it should be crushed to reduce and homogenize its particle size and improve its reuse value. Generally speaking, in this article, it should be crushed to a particle size of no more than 100 meshes because it needs to be acid-leached to obtain a steel slag leachate. It should be supplemented that there are currently commercially available powders that are obtained by crushing steel slag. The present invention can also directly select such commercially available powders that meet the specification of a particle size of no more than 100 meshes.

[0020] In this article, the steel slag described in step (1) is pre-treated including crushing, and the crushing method is a conventional ore raw material crushing process; depending on the source of the steel slag, technical personnel in this field should know that conventional steel slag pretreatment technology is a prerequisite technology for resource utilization of steel slag, so in addition to crushing, it usually also includes necessary conventional pretreatment of steel slag. Technical personnel in this field can consult the existing technology related to the steelmaking process for processing, which will not be repeated here.

[0021] In this article, the powder to be leached in step (2) is treated with acid leaching to obtain a slag leachate, which is mainly aimed at extracting metal elements from the slag by acid leaching to obtain the slag leachate, which is one of the conventional treatment methods for resource utilization of slag. Those skilled in the art can select suitable acid leaching solutions and acid leaching processes according to existing technical documents or conventional processes. It should be noted that the main purpose of the present invention is to utilize the complex special ratio of metal elements in the slag leachate to meet the preparation of adsorption / catalytic dual-functional materials for water-gas shift hydrogen production. Therefore, although the selection of acid leaching solutions and acid leaching processes will affect the concentration of metal elements in the slag leachate and the leaching efficiency, the above-mentioned effects can be adjusted and selected through existing technologies, which is not the main inventive point of the present invention.

[0022] In order to better illustrate the present invention and provide a technical solution for reference under laboratory conditions, the powder to be leached in step (2) is treated with acid leaching, wherein the acid leaching treatment specifically comprises first preparing 100 mL of nitric acid solution with a concentration of 4 to 5 mol / L, heating it to 60 to 90° C. in a water bath, adding 5 g of the powder to be leached, maintaining the water bath temperature and stirring and mixing for 1 to 1.5 hours, and filtering to obtain a steel slag leachate after the time is up.

[0023] In this article, the leaching concentration of Fe, Mn, Ca, Mg, and Al elements in the steel slag leachate obtained according to step (2) in step (3), wherein the leaching concentration of Fe, Mn, Ca, Mg, and Al elements is obtained by a conventional metal element analysis method in a solution in the chemical industry, for example, by ultraviolet-visible spectrophotometer, atomic absorption spectrometry, X-ray fluorescence spectrometry, or inductively coupled plasma mass spectrometry.

[0024] It should be noted that due to the different sources of steel slag, the leaching concentrations of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate from different sources of steel slag may be different. If necessary, in one of the technical solutions, the steel slag leachate can be diluted or concentrated to be as close to the requirements of the present invention as possible (the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg satisfy 2.4-8, 20-21.55, 5-5.8 and 4-4.5 respectively, and the leaching concentration of calcium element is 10-18.2 g / L).

[0025] In this article, step (3) is described by adding any one or more soluble iron salts, manganese salts, calcium salts, magnesium salts, and aluminum salts to the steel slag leachate. Whether to add the above-mentioned iron salts, manganese salts, calcium salts, magnesium salts, and aluminum salts and how much to add are all based on whether the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al, and Ca:Mg meet 2.4-8, 20-21.55, 5-5.8, and 4-4.5, respectively, and whether the leaching concentration of calcium element is 10-18.2 g / L. If the current metal element already meets the above requirements, the corresponding metal salt is not added. If it does not meet the above requirements, the corresponding metal salt is added.

[0026] For better explanation, taking the steel slag leachate used in the embodiment of the present invention as an example, the Shimadzu UV-2600 ultraviolet-visible spectrophotometer was used to analyze Fe, Mn, Ca, Mg, and Al in the steel slag leachate, and the leaching concentration of Fe element was 3.18 g / L, the leaching concentration of Mn element was 1.16 g / L, the leaching concentration of Ca element was 8.2 g / L, the leaching concentration of Mg element was 2.4 g / L, and the leaching concentration of Al element was 2.1 g / L. According to the required leaching concentration of calcium element of 10 to 18.2 g / L, 1.06 to 5.9 g of calcium nitrate tetrahydrate was added as a calcium salt, and according to the required Ca:Fe molar ratio of 2.4 to 8, 0 to 5.37 g of ferric nitrate nonahydrate was added to the solution as an iron salt, and there was no need to add manganese salt, magnesium salt and aluminum salt.

[0027] In this article, the iron salt, manganese salt, calcium salt, magnesium salt and aluminum salt in step (3) are conventional metal salt raw materials in the chemical industry. It should be noted that the metal salt that can be dissolved in the steel slag leachate should be selected.

[0028] In one of the technical solutions, the iron salt selected in step (3) includes any one or more of ferric nitrate nonahydrate, ferric chloride hexahydrate, and ferric acetate tetrahydrate.

[0029] In one technical solution, the manganese salt in step (3) is selected from any one or more of manganese nitrate solution, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate.

[0030] In one technical solution, the calcium salt selected in step (3) includes any one or more of hydrated calcium acetate and calcium nitrate tetrahydrate.

[0031] In one technical solution, the magnesium salt selected in step (3) includes any one or more of magnesium acetate tetrahydrate and magnesium nitrate hexahydrate.

[0032] In one of the technical solutions, the aluminum salt selected in step (3) includes any one or more of aluminum nitrate nonahydrate, aluminum chloride, and aluminum sulfate.

[0033] It should be noted that, since the mixed solution obtained in step (3) may precipitate when left to stand, if the operation is not continuous, it is recommended to stir the mixed solution at 70° C. for at least 30 min before adding in step (4), or to stir during the addition process.

[0034] In this article, the mixed solution and 0.4-0.6 mol / L NaOH solution in step (4) are simultaneously added dropwise to 0.1-0.2 mol / L NaCO3 solution. The mixed solution and the NaOH solution are added dropwise separately, but the NaOH solution should be added dropwise at any time along with the mixed solution until the mixed solution is completely dripped. During the dropping process, the pH of the reaction solution is controlled to be maintained at 10-11, and the pH value of the reaction solution can be monitored for control.

[0035] In one of the technical solutions, the dripping rate of the mixed solution in step (4) is preferably controlled at 1 to 2 drops / second.

[0036] In one of the technical solutions, the dripping rate of the NaOH solution in step (4) is preferably controlled at 2 to 3 drops / second, or adjusted by controlling the pH of the reaction solution to be maintained at 10 to 11.

[0037] In order to better illustrate the present invention and provide a technical solution for reference, the aging treatment is carried out accompanied by stirring in step (5), wherein the stirring is preferably accompanied by mechanical stirring at 150 to 200 r / min within 1 hour before the aging treatment, and the stirring is then stopped.

[0038] It should be noted that, according to research, the synthesis methods of adsorption / catalytic dual-functional materials in the prior art include impregnation, bio-template method, etc., but there is a common problem of short pre-breakthrough period in the water gas shift hydrogen production reaction, and the duration of the pre-breakthrough is related to the rapid carbonation reaction on the CaO surface. This stage achieves a higher CO conversion rate and H2 purity, so the longer duration of this stage is very important. With the increase in the thickness of the product layer, the reaction begins to enter the carbonation stage of CO2 in the material, which is the breakthrough stage, and the volume concentration of the remaining CO2 begins to gradually increase. In this stage, as the CO2 carbonation reaction rate decreases, the volume share of H2 and the CO conversion rate both decrease rapidly. When the reaction is completely in the stage of slow diffusion control, the volume share of each gas component is maintained in a relatively stable state.

[0039] The experiment found that the bifunctional materials prepared by using only steel slag or steel slag leaching solution have very low adsorption and catalytic abilities. Pure steel slag (specific surface area: 5.14m 3 / g) The capacity of CO2 adsorption can only reach 0.014g / g.

[0040] The main inventive point of the present invention is that the steel slag, which is based on industrial solid waste, contains rich metal elements. The steel slag contains elements Fe and Mn which can be used as catalytic elements, Ca and Mg which can be used as adsorption elements, and Al which can be used as an element to enhance the stability of the material. Pure steel slag has very low adsorption and catalytic abilities. Therefore, the steel slag is acid-leached to extract useful elements, and an adsorption / catalytic dual-functional material is prepared based on the leachate for use in the water-gas shift hydrogen production reaction of the synthesis gas obtained by biomass carbonization activation. In addition, based on experimental evidence, it is shown that the molar ratio of Ca / Fe in the steel slag leachate has an effect on the adsorption / catalytic properties of the material.

[0041] Secondly, the present invention provides a set of fixed ratios of Fe, Mn, Ca, Mg, and Al elements based on the steel slag leachate, through which technicians can quantitatively supplement metal salts in the steel slag leachate, thereby preparing adsorption / catalysis dual-functional materials in a simple and quick manner based on steel slag from different sources as a single raw material. In one embodiment, the prepared adsorption / catalysis dual-functional material can adsorb 0.105g / g of CO2 at a temperature of 600°C, promote CO conversion rate / hydrogen production rate of 83.1%, and pre-breakthrough period of 2h, far exceeding the pre-breakthrough period of only 1h for similar products.

[0042] After further comparative tests, it was surprisingly found that compared with the adsorption / catalysis dual-function material comparison sample prepared by impregnation with the verification solution obtained by dissolving metal salts with the same metal element ratio, the embodiment of the present invention still has a relatively obvious advantage. It is speculated that this is because the trace metal elements in the steel slag promote the adsorption / catalysis performance. Therefore, the present invention provides a new way to recycle and reuse steel slag at a high value, and can serve as a foundation for the subsequent technical development.

[0043] In this article, the filtering, washing and drying all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations according to common knowledge.

[0044] The present invention has the following beneficial effects:

[0045] 1. The present invention provides an adsorption / catalytic dual-functional material for water-gas shift hydrogen production and a preparation method thereof. The adsorption / catalytic dual-functional material is prepared by proportioning the metal elements in the steel slag leachate. The adsorption amount of CO2 can reach 0.105 g / g under the temperature condition of 600°C, the CO conversion rate / hydrogen production rate can reach 83.1%, and the pre-breakthrough period is 2 hours.

[0046] 2. The present invention provides an adsorption / catalytic bifunctional material for water-gas shift hydrogen production and a preparation method thereof, which improves the adsorption / catalytic capacity and pre-breakthrough time of the bifunctional material by utilizing a fixed ratio of Fe, Mn, Ca, Mg, and Al elements in the steel slag leachate.

[0047] 3. The overall process of the present invention is simple and easy to operate, the raw material cost is very low, the adsorption / catalytic performance of the material is stable, the reaction pre-breakthrough period lasts for a long time, and it has excellent application prospects. It provides a new way for high-value recycling and reuse of steel slag and can serve as the foundation for subsequent technological development.

[0048] 4. The adsorption / catalytic dual-functional material prepared by the present invention addresses the problem of high carbon emissions from producing synthesis gas from fossil fuels. The synthesis gas obtained during the activation of biochar is used as the raw gas for water-gas shift hydrogen production, thereby reducing carbon emissions from the source and lowering the greenhouse effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a comparison curve of the adsorption capacity of CO2 of the samples of Example 1, Example 2 and Comparative Example 1 of the present invention.

[0050] Figure 2 It is a dotted line graph comparing the cyclic adsorption capacity of CO2 of the samples of Example 1, Example 2 and Comparative Example 1 of the present invention.

[0051] Figure 3It is a dotted line graph comparing the CO conversion rates of samples in Example 1, Example 2 and Comparative Example 1 of the present invention.

[0052] Figure 4 It is a dotted line graph comparing the CO-promoting H2 production rates of the samples of Example 1, Example 2 and Comparative Example 1 of the present invention.

[0053] Figure 5 This is a graph showing the stability test results of the adsorption / catalytic dual-functional material for hydrogen production by water gas shift prepared in Example 1 of the present invention.

[0054] Figure 6 This is a graph showing the composition analysis results of bamboo pyrolysis gas and bamboo charcoal activation gas collected in the testing method of the present invention. DETAILED DESCRIPTION

[0055] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0056] A method for preparing an adsorption / catalysis dual-functional material for water gas shift hydrogen production mainly comprises the following steps:

[0057] (1) subjecting the recovered steel slag to a pretreatment including crushing to obtain a powder to be leached with a particle size of 40 to 100 meshes;

[0058] (2) subjecting the powder to be leached obtained in step (1) to acid leaching to obtain a steel slag leachate;

[0059] (3) according to the leaching concentration of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate obtained in step (2), any one or more of soluble iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts are added to the steel slag leachate, so that the molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg in the obtained mixed solution meet 2.4-8, 20-21.55, 5-5.8 and 4-4.5 respectively, and the leaching concentration of calcium element is 10-18.2 g / L;

[0060] (4) adding the mixed solution obtained in step (3) and a 0.4-0.6 mol / L NaOH solution to a 0.1-0.2 mol / L NaCO3 solution simultaneously until the mixed solution is completely dripped, and during the dripping process, the pH of the reaction solution is controlled to be maintained at 10-11, to obtain a precursor solution;

[0061] The volume ratio of the mixed solution obtained in step (3) to the NaCO3 solution is 1:(0.7-1.3);

[0062] (5) aging the precursor liquid obtained in step (4) at 65 to 80° C. for 4 to 6 hours with stirring, and filtering, washing, and drying to obtain a precursor solid after the time is up;

[0063] (6) calcining the precursor solid obtained in step (5) to obtain an adsorption / catalytic dual-functional material for water gas shift hydrogen production;

[0064] The calcination is specifically carried out by heating the temperature to 500-550° C. at a rate of 2-5° C. / min and calcining for 3-4 hours.

[0065] In this article, the steel slag described in step (1) is an industrial solid waste generated during the steelmaking process. It should be noted that, depending on the different steelmaking processes, the steel slag produced has different particle sizes. Before recycling and reuse, it should be crushed to reduce and homogenize its particle size and improve its reuse value. Generally speaking, in this article, it should be crushed to a particle size of no more than 100 meshes because it needs to be acid-leached to obtain a steel slag leachate. It should be supplemented that there are currently commercially available powders that are obtained by crushing steel slag. In one embodiment, the present invention can also directly select such commercially available powders that meet the specification of a particle size of no more than 100 meshes.

[0066] In this article, the steel slag described in step (1) is pre-treated including crushing, and the crushing method is a conventional ore raw material crushing process; depending on the source of the steel slag, technical personnel in this field should know that conventional steel slag pretreatment technology is a prerequisite technology for resource utilization of steel slag, so in addition to crushing, it usually also includes necessary conventional pretreatment of steel slag. Technical personnel in this field can consult the existing technology related to the steelmaking process for processing, which will not be repeated here.

[0067] In this article, the powder to be leached in step (2) is treated with acid leaching to obtain a slag leachate, which is mainly aimed at extracting metal elements from the slag by acid leaching to obtain the slag leachate, which is one of the conventional treatment methods for resource utilization of slag. Those skilled in the art can select suitable acid leaching solutions and acid leaching processes according to existing technical documents or conventional processes. It should be noted that the main purpose of the present invention is to utilize the complex special ratio of metal elements in the slag leachate to meet the preparation of adsorption / catalytic dual-functional materials for water-gas shift hydrogen production. Therefore, although the selection of acid leaching solutions and acid leaching processes will affect the concentration of metal elements in the slag leachate and the leaching efficiency, the above-mentioned effects can be adjusted and selected through existing technologies, which is not the main inventive point of the present invention.

[0068] In order to better illustrate the present invention and provide an implementation method for reference under laboratory conditions, the powder to be leached in step (2) is treated with acid leaching, wherein the acid leaching treatment specifically comprises first preparing 100 mL of nitric acid solution with a concentration of 4 to 5 mol / L, heating it to 60 to 90° C. in a water bath, adding 5 g of the powder to be leached, maintaining the water bath temperature and stirring and mixing for 1 to 1.5 hours, and filtering to obtain a steel slag leachate after the time is up.

[0069] In this article, the leaching concentration of Fe, Mn, Ca, Mg, and Al elements in the steel slag leachate obtained according to step (2) in step (3), wherein the leaching concentration of Fe, Mn, Ca, Mg, and Al elements is obtained by a conventional metal element analysis method in a solution in the chemical industry, for example, by ultraviolet-visible spectrophotometer, atomic absorption spectrometry, X-ray fluorescence spectrometry, or inductively coupled plasma mass spectrometry.

[0070] It should be noted that due to the different sources of steel slag, the leaching concentrations of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate from different sources of steel slag may be different. If necessary, in one embodiment, the steel slag leachate can be diluted or concentrated to be as close to the requirements of the present invention as possible (the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg satisfy 2.4-8, 20-21.55, 5-5.8 and 4-4.5 respectively, and the leaching concentration of calcium element is 10-18.2 g / L).

[0071] In this article, step (3) is described by adding any one or more soluble iron salts, manganese salts, calcium salts, magnesium salts, and aluminum salts to the steel slag leachate. Whether to add the above-mentioned iron salts, manganese salts, calcium salts, magnesium salts, and aluminum salts and how much to add are all based on whether the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al, and Ca:Mg meet 2.4-8, 20-21.55, 5-5.8, and 4-4.5, respectively, and whether the leaching concentration of calcium element is 10-18.2 g / L. If the current metal element already meets the above requirements, the corresponding metal salt is not added. If it does not meet the above requirements, the corresponding metal salt is added.

[0072] For better explanation, taking the steel slag leachate used in the embodiment of the present invention as an example, the Shimadzu UV-2600 ultraviolet-visible spectrophotometer was used to analyze Fe, Mn, Ca, Mg, and Al in the steel slag leachate, and the leaching concentration of Fe element was 3.18 g / L, the leaching concentration of Mn element was 1.16 g / L, the leaching concentration of Ca element was 8.2 g / L, the leaching concentration of Mg element was 2.4 g / L, and the leaching concentration of Al element was 2.1 g / L. According to the required leaching concentration of calcium element of 10 to 18.2 g / L, 1.06 to 5.9 g of calcium nitrate tetrahydrate was added as a calcium salt, and according to the required Ca:Fe molar ratio of 2.4 to 8, 0 to 5.37 g of ferric nitrate nonahydrate was added to the solution as an iron salt, and there was no need to add manganese salt, magnesium salt and aluminum salt.

[0073] In this article, the iron salt, manganese salt, calcium salt, magnesium salt and aluminum salt in step (3) are conventional metal salt raw materials in the chemical industry. It should be noted that the metal salt that can be dissolved in the steel slag leachate should be selected.

[0074] In one embodiment, the iron salt selected in step (3) includes any one or more of ferric nitrate nonahydrate, ferric chloride hexahydrate, and ferric acetate tetrahydrate.

[0075] In one embodiment, the manganese salt in step (3) includes any one or more of manganese nitrate solution, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate.

[0076] In one embodiment, the calcium salt selected in step (3) includes any one or more of hydrated calcium acetate and calcium nitrate tetrahydrate.

[0077] In one embodiment, the magnesium salt selected in step (3) includes any one or more of magnesium acetate tetrahydrate and magnesium nitrate hexahydrate.

[0078] In one embodiment, the aluminum salt selected in step (3) includes any one or more of aluminum nitrate nonahydrate, aluminum chloride, and aluminum sulfate.

[0079] It should be noted that, since the mixed solution obtained in step (3) may precipitate when left to stand, if the operation is not continuous, in one embodiment, it is recommended to stir the mixed solution at 70° C. for at least 30 min before adding in step (4), or to stir the mixed solution during the addition process.

[0080] In this article, the mixed solution and 0.4-0.6 mol / L NaOH solution in step (4) are simultaneously added dropwise to 0.1-0.2 mol / L NaCO3 solution. The mixed solution and the NaOH solution are added dropwise separately, but the NaOH solution should be added dropwise at any time along with the mixed solution until the mixed solution is completely dripped. During the dropping process, the pH of the reaction solution is controlled to be maintained at 10-11, and the pH value of the reaction solution can be monitored for control.

[0081] In one embodiment, the dripping rate of the mixed solution in step (4) is preferably controlled at 1 to 2 drops / second.

[0082] In one embodiment, the dripping rate of the NaOH solution in step (4) is preferably controlled at 2 to 3 drops / second, or adjusted according to controlling the pH of the reaction solution to be maintained at 10 to 11.

[0083] In order to better illustrate the present invention and provide an implementation method for reference, the aging treatment is carried out accompanied by stirring in step (5), wherein the stirring is preferably accompanied by mechanical stirring at 150 to 200 r / min within 1 hour before the aging treatment, and the stirring is then stopped.

[0084] It should be noted that, according to research, the synthesis methods of adsorption / catalytic dual-functional materials in the prior art include impregnation, bio-template method, etc., but there is a common problem of short pre-breakthrough period in the water gas shift hydrogen production reaction, and the duration of the pre-breakthrough is related to the rapid carbonation reaction on the CaO surface. This stage achieves a higher CO conversion rate and H2 purity, so the longer duration of this stage is very important. With the increase in the thickness of the product layer, the reaction begins to enter the carbonation stage of CO2 in the material, which is the breakthrough stage, and the volume concentration of the remaining CO2 begins to gradually increase. In this stage, as the CO2 carbonation reaction rate decreases, the volume share of H2 and the CO conversion rate both decrease rapidly. When the reaction is completely in the stage of slow diffusion control, the volume share of each gas component is maintained in a relatively stable state.

[0085] The experiment found that the bifunctional materials prepared by using only steel slag or steel slag leaching solution have very low adsorption and catalytic abilities. Pure steel slag (specific surface area: 5.14m 3 / g) The capacity of CO2 adsorption can only reach 0.014g / g.

[0086] The main inventive point of the present invention is that the steel slag, which is based on industrial solid waste, contains rich metal elements. The steel slag contains elements Fe and Mn which can be used as catalytic elements, Ca and Mg which can be used as adsorption elements, and Al which can be used as an element to enhance the stability of the material. Pure steel slag has very low adsorption and catalytic abilities. Therefore, the steel slag is acid-leached to extract useful elements, and an adsorption / catalytic dual-functional material is prepared based on the leachate for use in the water-gas shift hydrogen production reaction of the synthesis gas obtained by biomass carbonization activation. In addition, based on experimental evidence, it is shown that the molar ratio of Ca / Fe in the steel slag leachate has an effect on the adsorption / catalytic properties of the material.

[0087] Secondly, the present invention provides a set of fixed ratios of Fe, Mn, Ca, Mg, and Al elements based on the steel slag leachate, through which technicians can quantitatively supplement metal salts in the steel slag leachate, thereby preparing adsorption / catalysis dual-functional materials in a simple and quick manner based on steel slag from different sources as a single raw material. In one embodiment, the prepared adsorption / catalysis dual-functional material can adsorb 0.105g / g of CO2 at a temperature of 600°C, promote CO conversion rate / hydrogen production rate of 83.1%, and pre-breakthrough period of 2h, far exceeding the pre-breakthrough period of only 1h for similar products.

[0088] After further comparative tests, it was surprisingly found that compared with the adsorption / catalysis dual-function material comparison sample prepared by impregnation with the verification solution obtained by dissolving metal salts with the same metal element ratio, the embodiment of the present invention still has a relatively obvious advantage. It is speculated that this is because the trace metal elements in the steel slag promote the adsorption / catalysis performance. Therefore, the present invention provides a new way to recycle and reuse steel slag at a high value, and can serve as a foundation for the subsequent technical development.

[0089] In this article, the filtering, washing and drying all follow the conventional principles in chemical processes, and those skilled in the art can perform specific operations according to common knowledge.

[0090] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0091] Example

[0092] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0093] 1. Raw materials

[0094] The steel slag powder is provided by Henan Borun Casting Materials Co., Ltd. The particle size of the steel slag powder is 40-100 meshes. The main chemical composition is shown in Table 1:

[0095] Table 1 Main chemical composition of steel slag

[0096]

[0097] The reagents used are shown in Table 2 below:

[0098] Material Name concentration Manufacturer <![CDATA[HNO3]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. <![CDATA[Ca(NO3)2·4H2O]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. <![CDATA[Fe(NO3)3·9H2O]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. NaOH Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd. <![CDATA[anhydrous Na2CO3]]> Analytical grade Shanghai Aladdin Biochemical Technology Co., Ltd.

[0099] 2. Preparation method

[0100] (1) directly using steel slag powder with a particle size of 40 to 100 mesh as the powder to be leached;

[0101] (2) subjecting the powder to be leached obtained in step (1) to acid leaching to obtain a steel slag leachate;

[0102] The acid leaching treatment specifically comprises the following steps: firstly preparing 100 mL of nitric acid solution with a concentration of 4 mol / L, heating it to 70°C in a water bath, adding 5 g of the powder to be leached, maintaining the water bath temperature and stirring and mixing for 1 hour, and filtering to obtain the steel slag leachate after the time is up;

[0103] (3) according to the leaching concentration of Fe, Mn, Ca, Mg and Al elements in the steel slag leachate obtained in step (2), 5.9 g of calcium nitrate tetrahydrate is added to the steel slag leachate, and according to the required Ca / Fe molar ratio of 5, 1.38 g of ferric nitrate nonahydrate is added so that the molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg in the obtained mixed solution are 5, 20, 5 and 4, and the leaching concentration of calcium element is 18.2 g / L;

[0104] (4) the mixed solution obtained in step (3) and 0.6 mol / L NaOH solution are simultaneously added dropwise to 0.15 mol / L NaCO3 solution until the mixed solution is completely added, and the pH of the reaction solution is controlled to be maintained at 10 to 11 during the addition process to obtain a precursor solution;

[0105] The volume ratio of the mixed solution obtained in step (3) to the NaCO3 solution is 1:1;

[0106] The drop rate of the mixed solution is controlled at 1 drop / second;

[0107] (5) subjecting the precursor liquid obtained in step (4) to an aging treatment at 65° C. for 4 h with stirring, and after the aging treatment, filtering, washing, and drying to obtain a precursor solid;

[0108] The stirring is preferably accompanied by mechanical stirring at 150 r / min within 1 hour before the aging treatment, and then the stirring is stopped;

[0109] (6) calcining the precursor solid obtained in step (5) to obtain an adsorption / catalytic dual-functional material for water gas shift hydrogen production;

[0110] The calcination is specifically carried out by heating the temperature to 500° C. at a rate of 5° C. / min and calcining for 4 hours.

[0111] 3. Test Methods

[0112] (1) Bamboo pyrolysis gas / bamboo charcoal activation gas was collected in the factory using an air bag and then passed into a chromatograph (Fuli GC9790Plus) for detection.

[0113] (2) The N2 adsorption-desorption test was carried out in an American Microstation extended specific surface and porosity analyzer ASAP2460. Before the sample test, it was first degassed at 300°C in vacuum for 6 h to remove substances such as water and air adsorbed on the sample surface. Then, adsorption / desorption was carried out at liquid nitrogen temperature (77 K) to obtain the nitrogen adsorption-desorption isotherm. The specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method, and the pore volume and pore size distribution were calculated using the Barrett-Joyner-Halenda (BJH) method.

[0114] (3) The material's CO2 adsorption capacity and cyclic adsorption stability were analyzed using a SDT-Q600 synchronous thermogravimetric analyzer. The material was calcined at 920°C at a rate of 10°C / min in an Ar atmosphere for 20 min and then dropped to 600°C. The material was then switched to a CO2 atmosphere for adsorption for 30 min.

[0115] The CO2 adsorption capacity of the sample is calculated using the following formula (1):

[0116]

[0117] Where N is the number of cycles; C N Indicates the CO2 capture capacity of the sample in the Nth cycle, g / g; m 0,N+1 and m carb,N+1Respectively represent the mass of the sample after the N+1th calcination and carbonization reaction, g.

[0118] (4) Evaluation of material adsorption / catalytic performance: The water gas shift reaction was carried out in a fixed bed reactor, which was divided into three sections: heating section, insulation section and reaction section. 300 mg of the dual-functional material was mixed with 200 mg of SiO2 and loaded into a stainless steel tube reactor with an inner diameter of 10 mm supported by quartz wool. The WGSR reaction performance test was carried out under normal pressure. The reaction temperature was 600°C, and H2O / CO was maintained at 6. The flow rate of liquid water was controlled by a liquid chromatography pump and evaporated through the heating section and insulation section at 130°C. Before the reaction, the material was heated to the reaction temperature in Ar at a heating rate of 10°C / min. After reaching the specified temperature, a mixed gas with a total flow rate of 100 ml / min was introduced, in which the CO concentration was 4% (N2: 46%), and the reaction lasted for two hours. The product gas was cooled in an ice-water bath, and then dried on silica gel to remove moisture before entering a gas chromatograph (GC7890, Shandong Pucheng Instrument) equipped with a thermal conductivity detector TCD for detection. The chromatographic data was collected once every 14 minutes.

[0119] The relative concentrations of CO, CO2, H2 and CH4 in the product gas are calculated according to formula (2):

[0120]

[0121] Where i represents each gas component, CO, CO2, CH4, H2; V i represents the volume concentration of each gas in the above four gases, %; v i The calculation formulas for the volume concentration of each gas detected by gas chromatography, CO conversion rate and H2 yield are as follows:

[0122]

[0123] Where, X CO represents the conversion rate of CO, Y H2 represents the yield of H2, F CO,in and F N2,in represents the inlet flow rate of CO and N2, F CO,out and F H2,out Represents the outlet flow rates of CO and H2.

[0124] Example 1

[0125] Example 1 is to prepare an adsorption / catalytic dual-functional material for hydrogen production by water gas shift as a sample according to the above-mentioned "2. Preparation method" steps.

[0126] Example 2

[0127] Example 2 follows the steps of "2. Preparation method" above, but adds 0.77 g of ferric nitrate nonahydrate in step (3) so that the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al, and Ca:Mg in the resulting mixed solution are 6, 20, 5, and 4, and finally an adsorption / catalytic dual-functional material for water gas shift hydrogen production is prepared as a sample.

[0128] Comparative Example 1

[0129] Comparative Example 1 refers to the steps of "2. Preparation method" above, but in step (3), no calcium salt and iron salt are added, and the subsequent steps are directly performed as a mixed liquid, and the material finally prepared is used as a comparative sample.

[0130] The samples obtained in Example 1, Example 2 and Comparative Example 1 were tested according to the above “3. Test Method”, and the test results are as follows:

[0131] As shown in Table 3 below, the specific surface area and total pore volume of the sample in Example 1 are the largest, while the sample in Comparative Example 1 is the smallest; Figure 1 , 2 As shown, the adsorption capacity of the sample in Example 1 is the best, reaching 0.105 g / g, and it is still maintained at 0.08 g / g after 9 cycles. The adsorption capacity of the sample in Example 2 is 0.084 g / g, and it is maintained at 0.063 g / g after 9 cycles. The adsorption capacity of the sample in Comparative Example 1 is the worst, which is 0.06 g / g, and it is maintained at 0.04 g / g after 9 cycles. Figure 3 , 4 As shown, the sample in Example 1 has the best performance in promoting CO to produce hydrogen and decarbonization, with the CO conversion rate and H2 yield both reaching 84.1%, and the volume of CO2 remaining after the reaction accounting for 18.05%; the sample in Example 2 has the CO conversion rate and H2 yield both reaching 72.52%, and the volume of CO2 remaining after the reaction accounts for 25.25%; the sample in Comparative Example 1 has the worst performance in promoting CO to produce hydrogen and decarbonization, with the CO conversion rate and H2 yield both reaching 64.46%, and the volume of CO2 remaining after the reaction accounts for 28.48%.

[0132] like Figure 5 As shown, the pre-breakthrough time of the sample obtained in Example 1 reaches 2 hours.

[0133] Table 3 Structural parameters of samples

[0134]

[0135] Comparative Example 2

[0136] Comparative Example 2 is a verification comparative example. According to the ratio of Fe, Mn, Ca, Mg and Al elements proposed in the present invention, a water gas shift hydrogen production adsorption / catalytic dual-functional material prepared by impregnation with a verification solution prepared by dissolving a metal salt is used as a verification comparison sample. The specific preparation steps are as follows:

[0137] (1) Weighing calcium nitrate tetrahydrate, ferric nitrate nonahydrate, aluminum nitrate nonahydrate, manganese nitrate tetrahydrate, and magnesium nitrate hexahydrate respectively, adding them to 100 ml of deionized water to dissolve and mix them to form a mixed solution, so that the element molar ratios of Ca:Fe, Ca:Mn, Ca:Al, and Ca:Mg in the mixed solution are 5, 20, 5, and 4, and the mass concentration of calcium element is 18.2 g / L;

[0138] (2) the mixed solution obtained in step (1) and 0.6 mol / L NaOH solution are simultaneously added dropwise to 0.15 mol / L NaCO3 solution until the mixed solution is completely added, and during the addition, the pH of the reaction solution is controlled to be maintained at 10 to 11, to obtain a precursor solution;

[0139] The volume ratio of the mixed solution obtained in step (1) to the NaCO3 solution is 1:1;

[0140] The drop rate of the mixed solution is controlled at 1 drop / second;

[0141] (3) aging the precursor liquid obtained in step (2) at 65° C. for 4 h with stirring, and filtering, washing, and drying to obtain a precursor solid after the aging time is up;

[0142] The stirring is preferably accompanied by mechanical stirring at 150 r / min within 1 hour before the aging treatment, and then the stirring is stopped;

[0143] (4) calcining the precursor solid obtained in step (3) to prepare an adsorption / catalytic dual-functional material for water gas shift hydrogen production;

[0144] The calcination is specifically carried out by heating the temperature to 500° C. at a rate of 5° C. / min and calcining for 4 hours.

[0145] After testing, the molar ratio and concentration of Fe, Mn, Ca, Mg, and Al in the mixed solution prepared in Comparative Example 2 are almost consistent with those in Example 1, but the performance of its sample is still inferior to that of Example 1. It is speculated that this is because the trace metal elements in the steel slag promote the adsorption / catalytic performance.

[0146] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing an adsorption / catalytic dual-functional material for water gas shift hydrogen production, characterized in that The main steps include: (1) subjecting the recovered steel slag to a pretreatment including crushing to obtain a powder to be leached with a particle size of 40 to 100 meshes; (2) subjecting the powder to be leached obtained in step (1) to acid leaching to obtain a steel slag leachate; (3) according to the leaching concentration of Fe, Mn, Ca, Mg and Al in the steel slag leachate obtained in step (2), any one or more of soluble iron salts, manganese salts, calcium salts, magnesium salts and aluminum salts are added to the steel slag leachate, so that the molar ratios of Ca:Fe, Ca:Mn, Ca:Al and Ca:Mg in the obtained mixed solution meet 2.4-8, 20-21.55, 5-5.8 and 4-4.5 respectively, and the leaching concentration of calcium element is 10-18.2 g / L; (4) adding the mixed solution obtained in step (3) and a 0.4-0.6 mol / L NaOH solution to a 0.1-0.2 mol / L NaCO3 solution simultaneously until the mixed solution is completely dripped, and during the dripping process, the pH of the reaction solution is controlled to be maintained at 10-11, to obtain a precursor solution; The volume ratio of the mixed solution obtained in step (3) to the NaCO3 solution is 1:(0.7-1.3); (5) aging the precursor liquid obtained in step (4) at 65 to 80° C. for 4 to 6 hours with stirring, and filtering, washing, and drying to obtain a precursor solid after the time is up; (6) calcining the precursor solid obtained in step (5) to obtain an adsorption / catalytic dual-functional material for water gas shift hydrogen production; The calcination is specifically carried out by heating the temperature to 500-550° C. at a rate of 2-5° C. / min and calcining for 3-4 hours.

2. The preparation method according to claim 1, characterized in that: The powder to be leached in step (2) is treated with acid leaching, wherein the acid leaching treatment is specifically to first prepare 100 mL of nitric acid solution with a concentration of 4 to 5 mol / L, heat it to 60 to 90° C. in a water bath, add 5 g of the powder to be leached, maintain the water bath temperature and stir and mix for 1 to 1.5 hours, and filter to obtain the steel slag leachate after the time is up.

3. The preparation method according to claim 1, characterized in that: Step (3) also includes diluting or concentrating the steel slag leachate.

4. The preparation method according to claim 1, characterized in that: The iron salt in step (3) includes any one or more of ferric nitrate nonahydrate, ferric chloride hexahydrate, and ferric acetate tetrahydrate; The manganese salt in step (3) includes any one or more of manganese nitrate solution, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate; The calcium salt in step (3) includes any one or more of hydrated calcium acetate and calcium nitrate tetrahydrate; The magnesium salt in step (3) includes any one or more of magnesium acetate tetrahydrate and magnesium nitrate hexahydrate; The aluminum salt in step (3) includes any one or more of aluminum nitrate nonahydrate, aluminum chloride, and aluminum sulfate.

5. The preparation method according to claim 1, characterized in that: The dripping rate of the mixed solution in step (4) is controlled at 1 to 2 drops per second.

6. The preparation method according to claim 1, characterized in that: The aging treatment is carried out with stirring in step (5), wherein the stirring is accompanied by mechanical stirring at 150 to 200 r / min within 1 hour before the aging treatment, and the stirring is stopped thereafter.

7. The water-gas-shift adsorption / catalysis dual-function material for hydrogen production prepared by the method for preparing the water-gas-shift adsorption / catalysis dual-function material for hydrogen production as claimed in claim 1.

8. The adsorption / catalytic dual-functional material for water-gas shift hydrogen production as claimed in claim 7 is applied to the field of water-gas shift hydrogen production.